2020
DOI: 10.3389/fimmu.2020.01763
|View full text |Cite
|
Sign up to set email alerts
|

Urine Donor–Derived Cell-Free DNA Helps Discriminate BK Polyomavirus-Associated Nephropathy in Kidney Transplant Recipients With BK Polyomavirus Infection

Abstract: Background: Studies have shown that plasma donor-derived cell-free DNA (dd-cfDNA) can predict renal allograft antibody-mediated rejection. This study was performed to evaluate the value of urine dd-cfDNA concentration and dd-cfDNA fraction (%) for discriminating BK polyomavirus-associated nephropathy (BKPyVAN) in kidney transplant recipients with urinary BK polyomavirus (BKPyV) infection. Methods: In this retrospective single-center observational study, we enrolled kidney transplant recipients who were diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Our results were consistent with those reported by Chen ( 13 ), that plasma GcfDNA (cp/mL) was more diagnostic efficient than GcfDNA percentage ( 9 , 26 ). With an AUC of 0.68 for pathologically proven BKPyVAN and an AUC of 0.62 for clinically diagnosed BKPyVAN, the ability of GcfDNA (cp/mL) at biopsy time to diagnose BKPyVAN was still relatively poor.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results were consistent with those reported by Chen ( 13 ), that plasma GcfDNA (cp/mL) was more diagnostic efficient than GcfDNA percentage ( 9 , 26 ). With an AUC of 0.68 for pathologically proven BKPyVAN and an AUC of 0.62 for clinically diagnosed BKPyVAN, the ability of GcfDNA (cp/mL) at biopsy time to diagnose BKPyVAN was still relatively poor.…”
Section: Discussionsupporting
confidence: 93%
“…Chen et al reported that urine GcfDNA concentration in BKPyVAN was higher than that in T cellmediated rejection (TCMR), borderline change, and negative biopsies (12). Chen et al reported that elevated urine GcfDNA levels may help to distinguish BKPyVAN in kidney transplant recipients with BKPyV viruria (13). Kant et al suggested that GcfDNA may be a useful noninvasive test to assess progression of BKPyV to BKPyVAN (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In addition, two recent studies have discussed a diagnostic value of dd-cfDNA and/or viral cfDNA in urine. 24,25 Beside quantification of dd-cfDNA, assessment of serum and urinary chemokines, in particular, C-X-C motif chemokine ligand (CXCL) 9…”
Section: Introductionmentioning
confidence: 99%
“…52 Another report of 93 renal transplant recipients showed that urinary dd cfDNA has the ability to distinguish acute rejection from viral infection with a sensitivity of 96%, specificity of 91%, and AUROC of 0.745 at a threshold of 0.84%. 53 This disparity may be explained by the ability of hepatocytes to have unlimited proliferation compared to stable cells as in renal parenchyma and cardiac muscle. Consequently, we see higher baseline levels of cfDNA in liver transplant recipients in the absence of hepatocyte damage.…”
Section: Genetic Biomarkersmentioning
confidence: 99%